Morphological characteristics of Pinus radiata, Picea abies and Pinus sylvestris / Mohd Madzuan Shafaraz Mahmud - Mahmud, Mohd Madzuan Shafaraz (Faculty of Applied Sciences, 2017)
The morphological characteristic of fiber can determine the properties and behavior of wood species as a raw material in production line. The softwood species from Pinus radiata, Picea abies and Pinus sylvestris has been widely used in pallet and furniture industry. All of these three pine wood were categorized under family of Pinaceae. However, there are lack of information and research study regarding the morphological characteristic of the wood. The main purposes of this study were to determine and compare the morphological characteristics of Pinus radiata, Picea abies and Pinus sylvestris. The wood sample was taken from CHEP (Malaysia) Sdn. Bhd. and the fiber maceration was conducted using sodium chlorite method. The experimental design was based on Randomized Block Design (RBD). The findings of the study show a highly significant different on the fiber diameter and lumen diameter while there is no significant evidence on the fiber length and cell wall thickness on the three soft wood species. In terms of felting power the Pinus sylvestris, Pinus radiata and Picea abies has good potential to be used in paper production, tissue and packaging material. Although, there are slightly concerned on the strength properties of Pinus sylvestris since the runkel ratio and flexibility ratio is not pass the standard value.